Identification and Functional Characterization of a Novel Immunomodulatory Protein From Morchella conica SH - Wu, Guogan; Sun, Yu; Deng, Tingshan; Song, Lili; Li, Peng; Zeng, Haijuan; Tang, Xueming (Frontiers in Immunology, 2020)
A new fungal immunomodulatory protein (FIP) was found in the precious medical and edible mushroom Morchella conica SH, defined as FIP-mco, which belongs to the FIP family. The cDNA sequence was cloned and expressed in the yeast Pichia Pastoris X33. FIP was purified by agarose Ni chromatography and determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and Western blot. Phylogenetic analyses of FIPs from different origins using Neighbour-Joining (NJ) were performed. It was found that FIP-mco belonged to a new branch of the FIP family and may evolved from a different ancestor compared with the most other FIPs. FIP-mco can inhibit the migration of human A549 and HepG2 cells at the concentration of 15 and 30 μg/mL respectively in vitro. FIP-mco inhibited the proliferation of A549 and HepG2 cells at the concentration of 15 and 5 μg/mL respectively. Further, FIP-mco can significantly reduce the expression levels of TNF-α, IL-1β and IL-6 in the THP1 cells (human myeloid leukemia mononuclear cells). The results indicated the prospect of FIP-mco from M. conica SH as an effective and feasible source for cancer therapeutic studies and medical applications.